Pembuatan Batubata Dengan Penambahan Campuran Fly Ash Dan Semen Tanpa Proses Pembakaran - Evevndi, Zulfan; Fadli, Ahmad; Drastinawati, Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Brick is one of material construction which have many application in making material building. The purpose of this research is to study the effect of fly ash addition and hardening time on mechanic characteristic of brick produced. Brick is formed by mixing cement, clay, water and fly ash with adding 0;0,3;0,6;0,9;1,2 kg weight. Brick formed let under room temperature for 7, 14 and 21 day long. The brick quality was measured from its compressive strength, porosity and it’s leached value . The compressive strength test showed that 0,6 kg fly ash addition that dry for 21 day was the the strongest where it’s value was 9,375 N/mm2. It was also found that porosity value getting higher for fly ash addition up to 0,6 kg weight. The highest porosity was 21,34 % found in 1,2 fly ash addition. The result of TCLP test shows that for Pb, Cu, Cr content is still below the quality standards based on PP No.85 TH 1999 and is still considered harmless. leachate value for Pb was 3,10 mg/L, 1,213 mg/L for Cr and 4,374 mg/L for Cu.Keyword : brick, fly ash, compressive strength, porosity, TCLP